2018
DOI: 10.2196/mhealth.8261
|View full text |Cite
|
Sign up to set email alerts
|

Describing the Process of Adopting Nutrition and Fitness Apps: Behavior Stage Model Approach

Abstract: BackgroundAlthough mobile technologies such as smartphone apps are promising means for motivating people to adopt a healthier lifestyle (mHealth apps), previous studies have shown low adoption and continued use rates. Developing the means to address this issue requires further understanding of mHealth app nonusers and adoption processes. This study utilized a stage model approach based on the Precaution Adoption Process Model (PAPM), which proposes that people pass through qualitatively different motivational … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(126 citation statements)
references
References 82 publications
(101 reference statements)
4
108
4
Order By: Relevance
“…While there are many apps available to help decrease caloric intake, most are time consuming due to the need to log in everything consumed on a daily basis; a feature that may decrease their popularity and usage (König, Sproesser, Schupp, & Renner, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While there are many apps available to help decrease caloric intake, most are time consuming due to the need to log in everything consumed on a daily basis; a feature that may decrease their popularity and usage (König, Sproesser, Schupp, & Renner, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These apps are seen as an inclusive and scalable support system for healthy food [7]. However, the prevalence of such apps remains limited and many suffer from self-selection bias [27] and low rates of retention [36]. Several factors appear to limit the impact of such technology-based interventions.…”
Section: Motivationmentioning
confidence: 99%
“…carrying bags or products [12,36]. Third, studies show that current diet-related mHealth are usually primarily retained by users with an above average interest in nutrition [28], an interest that is particularly not often prevalent amongst sociodemographic segments prone to diet-related diseases [13,27].…”
Section: Motivationmentioning
confidence: 99%
“…These include health apps in various areas, such as nutrition, fitness, wellness, diagnostics or therapy [25], but systematic studies in the area of mHealth are scarce [26][27][28], and studies also highlight missing user acceptance of nutrition apps, for which the relatively high usage effort might be a reason [29,30]. Rohde et al concluded that app usage in the long-term is influenced by user-and app-related acceptance factors.…”
Section: Digitalization and Mhealthmentioning
confidence: 99%